Pembuatan Mesin Cuci Tangan Tanpa Sentuh dan Video Pembelajaran Berbasis Daring - Mursalim; Zubair Saing (LLDikti Wilayah XII Maluku dan Maluku Utara, 2021)
The implementation of real work lectures is one of the community service activities that universities routinely perform to carry out the tri dharma (KKN). In carrying out these activities, the Civil Engineering study program at Atma Jaya Makassar University (UAJM) is always guided by the realities of modern society. The Covid-19 pandemic that has ravaged the world and Indonesia, particularly South Sulawesi, is a serious issue that must be addressed right away. Everyone is strongly advised to protect their health by always wearing a mask, washing their hands with soap, and maintaining social distance or 3M to stop the spread of this virus. Atma Jaya Makassar University's Community Service Program activities, particularly the Civil Engineering study program, aim to support the government program by producing touch hand washing machines. Furthermore, simple civil engineering learning programs are carried out online to provide the public with an understanding of the implementation of civil construction. This activity resulted in solutions based on academic studies of the community's needs, challenges, or problems, either directly or indirectly. There is a transfer of technology, science, and art to the community for the advancement of human dignity, gender equity, social inclusion, and the preservation of natural resources.